2019
DOI: 10.1080/13683500.2019.1696758
|View full text |Cite
|
Sign up to set email alerts
|

Current state and development of Airbnb accommodation offer in 167 countries

Abstract: The paper examines the size, structure, distribution, dynamics, and use of Airbnb accommodation offer in 167 countries. Web-scrapping Airbnb website in fall 2018 and 2019 resulted in a datasets on 5.7 million listings, including 3.6 million active listings which have been rented out (reviewed) during the last year. Listings are divided into four groups based on types of properties and numbers of offers hosted by one platform user. The results show that the platform is most commonly used to rent out entire apar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 47 publications
1
70
0
10
Order By: Relevance
“…In Nordic countries, individually owned Airbnb rental properties are growing significantly (Adamiak, 2018). Single homes (single-hosted entire homes/apartments) form the majority that Airbnb offers in these countries, such as Denmark (mainly), followed by Sweden, Norway and Finland, except Iceland (mixed, a high balance of single rooms, single homes, multi-rooms and multi-homes) (Adamiak, 2019). Some recent studies indicated that, contrary to single-unit hosts, multi-unit hosts devoted more time and attention into the operations of their room-sharing business and thus were more proficient in serving guests (Kwok & Xie, 2019).…”
Section: Growth Of Airbnb In Nordic Countries and The Dominance Of Simentioning
confidence: 99%
See 1 more Smart Citation
“…In Nordic countries, individually owned Airbnb rental properties are growing significantly (Adamiak, 2018). Single homes (single-hosted entire homes/apartments) form the majority that Airbnb offers in these countries, such as Denmark (mainly), followed by Sweden, Norway and Finland, except Iceland (mixed, a high balance of single rooms, single homes, multi-rooms and multi-homes) (Adamiak, 2019). Some recent studies indicated that, contrary to single-unit hosts, multi-unit hosts devoted more time and attention into the operations of their room-sharing business and thus were more proficient in serving guests (Kwok & Xie, 2019).…”
Section: Growth Of Airbnb In Nordic Countries and The Dominance Of Simentioning
confidence: 99%
“…Furthermore, the active listings in Denmark and Iceland surpassed in recent years (Adamiak, 2019). In the same vein, in 2017, Visit Sweden, Sweden's official tourism board, collaborated with Airbnb to turn the entire country into an Airbnb listing (Airbnb, 2017), while Airbnb represented 90% of the dwellings in Stockholm (Einefors, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Private and shared rooms are slightly more common in Denmark than in other countries. Multi-hosted properties account for one-fourth of the total supply, much less than in other parts of the world (Adamiak, 2019).…”
Section: Distribution Of Airbnb Listingsmentioning
confidence: 99%
“…At the beginning, Airbnb was designed to enable renting out spare room in one's home (Gallagher, 2017). Later, the offer of professionally hosted rental homes and apartments, as well as hotel rooms, dominated the platform (Adamiak, 2019;Dolnicar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…More generally, with more recent data (fall 2018 and 2019) of 5.7 million listings in 167 countries, it was noted that the platform is most commonly used to rent entire apartments by multihosts, and supply of professional hosts was growing more rapidly than that of p2p hosts (Adamiak, 2019). Concretely, the percent of entire homes exceeded 70%, whereas professional hosts owned more than 60% of listings.…”
Section: Market Expansionmentioning
confidence: 99%